Adequacy of vitamin D intakes in children and teenagers from the base diet, fortified foods and supplements - Black, Lucinda; Walton, J.; Flynn, A.; Kiely, M. (Cambridge University Press, 2013)
To describe vitamin D intakes in children and teenagers and the contribution from supplements and fortified foods in addition to the base diet. Analysis of 7 d weighed food records collected during the Children's and Teens’ National Nutrition Surveys in Ireland. Food composition data for vitamin D were updated from international analytical sources. Nationally representative cross-sectional dietary surveys. Children (n 594; 5–12 years) and teenagers (n 441; 13–17 years). Median vitamin D intakes were 1·9, 2·1 and 2·4 μg/d in 5–8-, 9–12- and 13–17-year-olds, respectively. The prevalence of vitamin D-containing supplement use was 21, 16 and 15 % in 5–8-, 9–12- and 13–17-year-olds and median intakes in users ranged from 6·0 to 6·7 μg/d. The prevalence of inadequate intakes, defined as the percentage with mean daily intakes below the Estimated Average Requirement of 10 μg/d, ranged from 88 to 96 % in supplement users. Foods fortified with vitamin D, mainly breakfast cereals, fat spreads and milk, were consumed by 71, 70 and 63 % of 5–8-, 9–12- and 13–17-year-olds. Non-supplement users who consumed vitamin D-fortified foods had median intakes of 1·9–2·5 μg/d, compared with 1·2–1·4 μg/d in those who did not consume fortified foods. It is currently not possible for children consuming the habitual diet to meet the US Institute of Medicine dietary reference intake for vitamin D. In the absence of nationally representative 25-hydroxyvitamin D data in children, the implications of this observation for prevalence of vitamin D deficiency and health consequences are speculative.